Müllerian duct cyst misdiagnosed as ovarian cyst: a rare case report - Singh, Alpana; Shree, Sneha; Mishra, Vandana; Radhakrishnan, Gita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
The Müllerian duct cyst is a remnant of the caudal ends of the fused embryologic paramesonephric ducts (or Müllerian ducts). Preoperative distinction of ovarian cyst from a Müllerian duct cyst is important and is based on visualization of the ipsilateral ovary separate from the mass. Müllerian duct cysts may also be mistaken as paratubal, paraovarian or peritoneal inclusion cysts and hydrosalpinx. Thus, preoperative diagnosis of Müllerian cyst of the uterus can be very challenging. However, with increased awareness, preoperative diagnosis of this condition should be possible by sonography. Laparoscopy is useful as a minimally invasive treatment to diagnose as well as resect the cyst at the same time. We present a rare case of Müllerian duct cyst misdiagnosed as ovarian cyst pre-operatively and managed laparoscopically. A 32 year old multiparous female presented with the complaint of lump and dull aching pain in lower abdomen since three months. A cystic mobile mass measuring 6X7 cm with smooth surface which corresponded to 16 weeks gravid uterus size was palpated arising from pelvis. Her pelvic ultrasonography revealed a 7X7 cm unilocular thin walled simple cyst in right ovary suggestive of serous cystadenoma. Her CA-125 was 5.3 IU/ml. She was taken up for laparoscopic ovarian cystectomy. Intra-operatively, a 7X7 cm cyst was seen arising from right lateral wall of uterus. Histopathology showed the cyst wall features consistent with a Müllerian duct cyst.